SELEKSI SISWA ELIGIBLE CALON PESERTA SNBP MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA SISWA SMA MUHAMMADIYAH KUDUS KELAS XII - sucimaula adelia; Eko Darmanto; Arif Setiawan (LPPM Universitas Abdurrab, 2026)
The selection of eligible students for the National Selection Based on Achievement (SNBP) at SMA Muhammadiyah Kudus requires an objective, structured, and accountable decision-making process. Manual selection may cause delays in data processing, calculation errors, and subjectivity because it tends to focus mainly on the average report card score. This study aims to develop a web-based Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method to determine eligible students for SNBP. The data used in this study consisted of 105 twelfth-grade students of SMA Muhammadiyah Kudus from classes XII F1, XII F2, XII F3, and XII F4. The assessment criteria include report card scores from semesters 1–5, score consistency, and class ranking. The AHP method is used to determine the priority weight of each criterion through a pairwise comparison matrix and consistency testing. The calculation results show that the report card score criterion obtains the highest weight of 0.6334, followed by score consistency with 0.2605, and class ranking with 0.1062. The Consistency Ratio (CR) value obtained is 0.033327, indicating that the pairwise comparison matrix is consistent because the CR value is less than 0.10. The system is developed using Laravel as the main application and Python as the calculation engine. The system provides features for student data management, CSV import, AHP matrix input, calculation details, ranking results, and report export. The results show that the system can assist guidance counselors and the principal in determining eligible students for SNBP more effectively, objectively, transparently, and measurably.